Tutaform: A Multimedia Form for Brazilian Deaf Users - Sales, Angelina; Reis, Luana; Araújo, Tiago; Aguiar, Yuska (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
Assistive Technology (AT) resources enable people with disabilities to have access to products, services and information, favoring inclusion in various spheres of society. To enhance the autonomy of people with disabilities in the use of such resources, it is important to conduct evaluations of these to ensure that they are in accordance with the needs and expectations of the target audience. It is common for user-based assessments to be based on questionnaires, interviews, or focus groups. However, these traditional strategies are inadequate when the users participating in the evaluation of the AT resource are deaf, not fluent in Portuguese. In order to guarantee the autonomy of the deaf user in the process of evaluating AT resources assigned to them, a solution of a multimedia and online questionnaire adapted to the Brazilian Sign Language (LIBRAS) was elaborated from interactions with teachers/interpreters of LIBRAS and people Deaf TUTAForm comprises questions for collecting data about the user's profile, their level of satisfaction and emotional state after the use of the resource under evaluation. In order to verify the suitability of TUTAForm with its potential users, experiments were carried out to observe the interaction of a two groups of 5 deaf participants in the use of the fork game in datilology and use VLibras-Mobile, followed by the application of TUTAForm. As a result, a good understanding of the contents was perceived, however suggestions were made to improve the representation of some options of answers, due to the confusion to understand the scales used to define levels of schooling and deafness, for example.